Satellite Earth Observations and Their Impact on Society and Policy - Onoda, Masami; Young, Oran R.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The result of a workshop bringing together an international advisory board of experts in science, satellite technologies, industry innovations, and public policy, this book addresses the current and future roles of satellite Earth observations in solving large-scale environmental problems. The book showcases the results of engaging distinct communities to enhance our ability to identify emerging problems and to administer international regimes created to solve them. It also reviews the work of the Policy and Earth Observation Innovation Cycle (PEOIC) project, an effort aimed at assessing the impact of satellite observations on environmental policy and to propose a mission going forward that would launch an (3z(Binnovation cycle(3y(B. The achievements of such a mission would feed back to innovations in next-generation observation technology, thus contributing to global policy demand for policy-relevant information. This book is open access under a CC BY license. .s
Satellite Earth Observations in Environmental Problem-Solving -- Policy and Earth Observation Innovation Cycle (PEOIC) Project (Japan) -- Innovation in Earth Observations as a National Strategic Investment: The Experience of the U.S -- Benefits Assessment of Applied Earth Science -- ESA$1 (Bs Earth Observation Strategy and Copernicus -- Earth Observation--UK Perspective and Policy -- Benefit Assessment of the Application of Satellite Earth Observation for Society and Policy: Assessing the Socio-economic Impacts of the Development of Downstream, Space-based Earth Observation Applications -- Chinese Earth Observation Program and Policy -- Greenhouse Gas Observation from Space -- Japanese Satellite Earth Observation: Status and Policy Issues -- The New 10-Year GEOSS Strategy for 2016 and Beyond -- The Value of Global Earth Observations -- Earth Observation Support to the UN Framework Convention on Climate Change: The Example of REDD+ -- Quantitative Assessment of the Earth Observation Data and Methods Used to Generate Reference Emission Levels for REDD+ -- Evaluation of Space Programs: Select Findings from the OECD Space Forum -- Integrating Earth Observation Systems and International Environmental Regimes -- Conclusion.s
Keywords: Environment; Geographic information systems; Climatology; Environmental Law; Environmental policy; Environmental Sciences; Geographical Information System; Climate Sciences; Environmental Law; Environmental Policy